1986
DOI: 10.1182/blood.v67.5.1448.1448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant human GM-CSF on proliferation of clonogenic cells in acute myeloblastic leukemia

Abstract: Proliferation of acute myeloblastic leukemia (AML) cells in vitro is limited in most cases to a small subset of blasts that have several properties of stem cells. These leukemic colony-forming cells (AML-CFU) generally require addition of exogenous growth factors for proliferation in agar or methylcellulose. These factors can be supplied by media conditioned by phytohemagglutinin-stimulated normal leukocytes or by CSF-secreting tumor cell lines. However, the exact factor or factors required for stimulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Some acute myelogenous leukemia (AML) cells have the ability to form colonies in a semisolid culture supplemented with conditioned media containing colonystimulation factors (Moore et al,, 1973;Griffin and Lo- , 1986). Furthermore, the proliferation of some AML cells has been supported by rhGM-CSF (Griffin et al, 1986;Hoang et al, 1986). The establishment of three GM-CSF-dependent cell lines (T-ALL-101, AML 193, and MV4-11) has been reported recently (Lange et al, 1987;Valtieri et al, 1987).…”
Section: Induction Of Differentiation By Various Agentsmentioning
confidence: 96%
“…Some acute myelogenous leukemia (AML) cells have the ability to form colonies in a semisolid culture supplemented with conditioned media containing colonystimulation factors (Moore et al,, 1973;Griffin and Lo- , 1986). Furthermore, the proliferation of some AML cells has been supported by rhGM-CSF (Griffin et al, 1986;Hoang et al, 1986). The establishment of three GM-CSF-dependent cell lines (T-ALL-101, AML 193, and MV4-11) has been reported recently (Lange et al, 1987;Valtieri et al, 1987).…”
Section: Induction Of Differentiation By Various Agentsmentioning
confidence: 96%
“…Despite their high proliferative rate in vivo, most leukemic cells do not grow well in tissue culture (Ferrero and Rovera, 1984). However, since the identification and purification of hemopoietic growth factors such as IL-3, GM-CSF, G-CSF, M-CSF, or cytokines such as IL-1 and IL-6, the short-term proliferation in vitro of AML cells isolated from patients has been more readily achieved (Griffin et al, 1986;Miyauchi et al, 1987). Most AML cells proliferate in the presence of G-CSF, GM-CSF, IL-3 (Santoli et al, 1987), or IL-I (Cozzolino et al, 1989;Delwel et al, 1989).…”
mentioning
confidence: 99%
“…Highly purified or recombinant CSF is a candidate for studying the regulation of the proliferation of the leukemic blast progenitors. Recently, the effects of recombinant GM-CSF on leukemic blast progenitors have been studied; recombinant GM-CSF supported the self-renewal and terminal divisions of blast progenitors from AML patients [10,11]. The data have demonstrated that a factor regulating normal granulopoiesis also stimulates the growth of the leukemic population.…”
Section: Introductionmentioning
confidence: 99%